Analisis Filosofis Tentang Ilmu Pengetahuan dalam Perspektif Filsafat Pendidikan Islam dan Implikasinya terhadap Pengembangan Pendidikan Islam - Rizal Safarudin; Zulfamanna Zulfamanna; Zulmuqim Zulmuqim; M Zalnur (Departement of Mathematics Education, 2022)
The purpose of this study is to find out and analyze the problems of science daperspective of the philosophy of Islamic education and its implications for the development of Islamic Education. Pen shapeThis is a descriptive qualitative library research. The data sources in this research are adbooks and journals that are relevant to this research. data collection techniques from document studiesand the data obtained is processed and concluded. The problem found is about the concept of Isknowledge of the development of Islamic Education. results of research on the concept of science daIslam, Dichotomy of Science, Islamization of Science, Integration and interconnection of knowledge and its implications for carriersIslamic studies